p75 Neurotrophin Receptor Expression Is Induced in Apoptotic Neurons After Seizure - Roux, Philippe P. (J Neurosci, 1999)
Seizure causes neuronal cell loss in both animal models and human epilepsy. To determine the contribution of apoptotic mechanisms to seizure-induced neuronal cell death, rat brains were examined for the occurrence of terminal deoxynucleotidyl transferase-mediated UTP nick end labeling (TUNEL)-positive nuclei after pilocarpine-induced seizure. Numerous TUNEL-positive cells were observed throughout the postseizure hippocampus, piriform cortex, and entorhinal cortex. Combined TUNEL/NeuN immunocytochemistry demonstrated that the vast majority of TUNEL-positive cells were neurons. To identify components of the signal transduction cascade promoting postseizure apoptosis, the expression of the p75 neurotrophin receptor (p75NTR) was examined. Seizure-induced increases in p75NTR protein and mRNA were detected in hippocampus, piriform cortex, and entorhinal cortex. Immunohistochemical double labeling revealed almost complete correspondence between TUNEL-positive and p75NTR-expressing cells, suggesting that seizure-induced neuronal loss within the CNS occurs through apoptotic signaling cascades involving p75NTR.